Sickle cell disease and maternity care: A qualitative synthesis of women’s and health providers experiences - Kenneth Finlayson; Gill Moncrieff; Cath Harris; Soo Downe (PLoS ONE, 2026)
Introduction Sickle Cell Disease (SCD) is one of the most prevalent genetic diseases in the world. For women with SCD or those with Sickle Cell Trait (SCT) reproductive choices not only require consideration of genetic inheritance but also the exacerbation of pregnancy induced SCD symptoms and potential birth complications. To explore these issues a qualitative synthesis was conducted incorporating the views of women with SCD or SCT as well as healthcare professionals working with these women in maternity settings. Methods Database searches were performed in MEDLINE, Embase, MIDIRS, CINAHL Ultimate, PsycINFO, Social Sciences Citation Index, Global Index Medicus and CNKI, as well as reference lists of included studies published January 2000–October 2024. Studies reporting qualitative data from women with SCD or SCT and health professionals providing care to these women during the maternity phase were included. Data Collection and Analysis Author findings were extracted, coded and synthesised using techniques derived from thematic synthesis. Confidence in the quality, coherence, relevance and adequacy of data underpinning the resulting findings was assessed using GRADE-CERQual. Results Eleven studies from four different countries (UK, Brazil, France and Uganda) were identified including eight focusing on the views of women, two reporting on the views of health professionals and one exploring both. From these four analytical themes were generated: Beyond the routine of antenatal screening; Myths, misunderstandings and submissiveness; Fear and uncertainty in the face of adversity; The importance of familial and organizational support . Confidence in the results was moderate to good. Conclusion The synthesis suggests that the intersection of SCD and maternity care is beset with a lack of understanding and inadequate health system support. In some contexts, women endure stigmatization, discrimination and poor quality care. Public awareness campaigns and educational initiatives, particularly amongst healthcare professionals, are urgently required to address these issues.